Industrial training report: Perpustakaan Tengku Anis / Amalia Lestari - Lestari, Amalia (Perpustakaan Tengku Anis, 2023)
Industrial training is one of the subjects that need to be taken by students as one of the requirement to finish bachelor’s degree. This report consists of Indonesian students’ experiences in industrial training at Perpustakaan Tengku Anis UiTM Kelantan Branch, Machang Campus, Malaysia. The industrial training took place hybrid from April – July 2023. The report discussed the experiences and lessons gained by the trainee in library field during her industrial training period, such as cataloguing process, records and archive management, bookbinding, corporate social responsibility, and so on. Hopefully, this report can be beneficial for the trainee, UiTM Kelantan Branch, Perpustakaan Tengku Anis, Universitas Airlangga, and general public regarding the field of Library and Information Science.